LIMBAH KULIT GARCINIA MANGOSTANA L.: TEROBOSAN BARU UNTUK PERLINDUNGAN TERHADAP SIROSIS HEPATIS - Rachman, Adelia Ulya; Wijaya, Marzuki Panji; Alvianita, Audesia; Hidayat, Putra Nur; Alamsjah, Jeffry (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Liver cirrhosis is caused by exposure of free radicals to the liver and can only be treated with a liver transplant. Previous studies mentioned that mangosteen (Garcinia Mangostana L.) pericarp contain antioxidant compounds. The aim of this study is to test the hepatoprotective ability of mangosteen pericarp to prevent liver cirrhosisâ progression.6 groups of mice will be given intervention and then the following parameters will be observed: serum ALT, AST, bilirubin and the histopathologic appearance of the miceâs liver. Of all four parameter that was observed, only the histopathologic appearance of the miceâs liver shows significant result.Keywords: mangosteen, cirrhosis, garcinia mangostana, herbal.